2002
DOI: 10.1002/pat.203
|View full text |Cite
|
Sign up to set email alerts
|

Stability of adsorber resins under mechanical compression and ultrasonication

Abstract: Different adsorber and ion exchange resins have been sonicated with ultrasound of different frequencies in a fixed bed. Afterwards, the sonicated particles were investigated by scanning electron and light microscopy. Also, different mechanical properties, like fracture load, maximum flattening and Young's modulus were measured in compression tests and compared to the results of the ultrasonication experiments. Cavitational collapses cause cracks in resins with a high fracture load and a high Young's modulus as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…The resin is in the form of chemical inert rigid spheres, which are wet sieved to particle sizes between 630 and 800 μm in these studies. Preliminary tests had shown that the resin does not get damaged by ultrasound of the applied frequencies …”
Section: Methodsmentioning
confidence: 99%
“…The resin is in the form of chemical inert rigid spheres, which are wet sieved to particle sizes between 630 and 800 μm in these studies. Preliminary tests had shown that the resin does not get damaged by ultrasound of the applied frequencies …”
Section: Methodsmentioning
confidence: 99%
“…The final data point indicates the total amount of product associated with the spent resin after its complete saturation with epothilone D. The total binding capacity of the resins for additional epothilone is highly dependent upon the nature of the production strain and process. Error bars indicate the standard deviation of each triplicate data set values for a single resin bead [2]. The XAD-16 resin was found to be the least ductile and most prone to fracture of the various resin types tested.…”
Section: Fracture Of Product Adsorption Resin During a Microbial Cultmentioning
confidence: 98%
“…A compression force of 1 N was required to fracture a representative XAD-16 resin bead under loading, while some of the other resin beads were able to withstand compression forces seven times higher. The polystyrene XAD-16 resin beads deform under a compression load by almost 25% of the bead diameter before fracture occurs [2], or by about 150 lm for an average bead. The threshold amount of work required over this deformation distance for a resin bead to fracture from a single impact is approximately 1.5·10 4 g cm 2 /s 2 , about six orders of magnitude higher than the actual bead-bead collision energy at an agitation rate of 800 rpm.…”
Section: Fracture Of Product Adsorption Resin During a Microbial Cultmentioning
confidence: 99%
“…These artificial soils (each 20 g) were stored in 100 mL of 1.6 g cm −3 dense SPT solution for 1 h in 200 mL PE bottles, which did not show measurable release of plastic fragments due to sonication in preliminary tests with a pure fine sand matrix (data not shown). Mechanical stress was applied by use of a sonotrode (Branson© Sonifier 250) as described by Büks and Kaupenjohann (2016). The sonication times corresponding to 0, 10, 50, 100 and 500 J mL −1 were determined by means of the sonotrode's energy output calculated following North (1976).…”
Section: Mechanical Stress Treatmentmentioning
confidence: 99%
“…The mechanical disintegration of soil aggregates by use of ultrasonication following the method of Edwards and Bremner (1967a) and subsequent density fractionation of particulate organic matter is widely used in the assessment of soil organic matter (SOM) stability. This includes characteristics such as aggregate composition and stability (Edwards and Bremner, 1967b), the constitution of SOM pools (Golchin et al, 1994), the stabilization of SOM in forest ecosystems (Graf-Rosenfellner et al, 2016) and the occlusive strength of particulate organic matter (POM) (Büks and Kaupenjohann, 2016). Ultrasonication is also applied to assess quantities and qualities of anthropogenic contaminants such as microplastics (Zhang and Liu, 2018;.…”
Section: Introductionmentioning
confidence: 99%